Duck Plague Hits Home - Scott, Lynnette (Wildlife Rehabilitation Bulletin, 2008)
In June, as many orphaned waterfowl cared for in WRCs waterfowl nursery reached the age of showing adult feathering, a series of sudden deaths occurred among older mallard ducklings (Anas platyrhynchos). Prior to finding these animals dead, none had exhibited any major abnormal health issues or symptoms. Laboratory findings indicated the ducks had died of duck plague (Duck Viral Enteritis).